The Influence of Brand Image and Digital Marketing on Indihome Provider Purchase Decisions in Sidoarjo - Khalik, Muhammad David; Supriyono, Supriyono; Hariyana, Nanik (Universitas KH. Abdul Chalim Mojokerto, 2026)
The telecommunications industry is often characterized by competition between providers. Brand image and digital marketing play a crucial role in influencing consumer choices. This study aims to analyze the impact of brand image and digital marketing on purchasing decisions for IndiHome service providers in the Sidoarjo area. The research approach used was quantitative, involving the distribution of questionnaires to 97 respondents who were IndiHome users in Sidoarjo. Data processing was performed using the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS) to highlight the relationships between these variables. The research findings revealed that brand image has a positive and meaningful impact on consumers' decisions to purchase IndiHome services. The indicator with the highest loading factor was the view that IndiHome is widely recognized and considered a superior internet provider. Furthermore, digital marketing also contributed significantly to supporting purchasing decisions, with the effectiveness of product communication and promotion through digital platforms being a determining factor. The results show that brand image has a significant influence on purchasing decisions with the highest indicator loading factor of 0.845 and a mean value of 4.443 in the statement